1997
DOI: 10.1073/pnas.94.8.3621
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of thioredoxin reductase from human placenta is similar to the mechanisms of lipoamide dehydrogenase and glutathione reductase and is distinct from the mechanism of thioredoxin reductase from Escherichia coli

Abstract: Thioredoxin reductase, lipoamide dehydrogenase, and glutathione reductase are members of the pyridine nucleotide-disulfide oxidoreductase family of dimeric f lavoenzymes. The mechanisms and structures of lipoamide dehydrogenase and glutathione reductase are alike irrespective of the source (subunit M r Ϸ55,000). Although the mechanism and structure of thioredoxin reductase from Escherichia coli are distinct (M r Ϸ35,000), this enzyme must be placed in the same family because there are significant amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
235
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(248 citation statements)
references
References 43 publications
13
235
0
Order By: Relevance
“…Absorption ratios A 280 nm / A 463 nm as well as extinction coefficients of the oxidized enzyme species at 463 nm were determined from spectral analyses (wild type hTrxR: e = 11.3 mM À1 cm À1 [2,3], hTrxR-16 K29R : e = 11.74 mM À1 cm À1 , hTrxRD16 K29R,H108Y : e = 13.87 mM À1 cm À1 , hTrxRD16 K29R,H108Y,A119N,V478E : e = 15.22 mM À1 cm À1 ). Oxidised hTrxR-16 had a typical flavoprotein spectrum [28] with peak absorption at 463 nm ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Absorption ratios A 280 nm / A 463 nm as well as extinction coefficients of the oxidized enzyme species at 463 nm were determined from spectral analyses (wild type hTrxR: e = 11.3 mM À1 cm À1 [2,3], hTrxR-16 K29R : e = 11.74 mM À1 cm À1 , hTrxRD16 K29R,H108Y : e = 13.87 mM À1 cm À1 , hTrxRD16 K29R,H108Y,A119N,V478E : e = 15.22 mM À1 cm À1 ). Oxidised hTrxR-16 had a typical flavoprotein spectrum [28] with peak absorption at 463 nm ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both motifs are essential for enzymatic activity with thioredoxin as substrate (10 -12, 19). Even though it has been proposed that there exists a high degree of structural similarity between the high M r TrxRs with glutathione reductase and lipoamide dehydrogenase (10,18), the catalytic mechanism of the TrxRs appears to be much more complicated than that of the latter enzymes. Wang et al (10,11) have shown that during catalysis reducing equivalents are transferred from FAD to the N-terminal pair of cysteines and subsequently reduce the C-terminal cysteine pair by an intramolecular dithiol/disulfide exchange.…”
Section: Expression and Purification Of Pftrxr Homo-and Heterodimers-mentioning
confidence: 99%
“…However, it had a 100-fold lower k cat and a 10-fold lower K m for Trx compared with the Se-containing wild-type rat enzyme (10). The truncated protein lacking the C-terminal SeCys-Gly dipeptide was also folded and contained FAD but was inactive although titration with NADPH yielded the characteristic thiolate-flavin charge transfer complex common for GR and mammalian TrxR (1,28). In this paper, we have identified a selenenylsulfide as the active site of TrxR and propose a structure model and mechanisms for the enzyme.…”
mentioning
confidence: 99%